Vitamin B12 in metformin-treated diabetic patients: a cross-sectional study in Brazil - Nervo,Monique (2011)
OBJECTIVE: The objective of this study was to evaluate the presence of vitamin B12 deficiency and the factors associated with serum vitamin B12 levels in a sample of metformin-treated Brazilian diabetic patients. METHOD: Cross-sectional study. RESULTS: 144 patients were included. Serum vitamin B12 levels were low (< 125 pmol/L) in 10 patients (6.9%) and possibly low (125 - 250 pmol/L) in 53 patients (36.8%). Serum vitamin B12 levels were negatively associated with age (B = -3.17; β= -0.171; p = 0.037) and duration of metformin use (B= -33.36; β= -0.161; p = 0.048), and positively associated with the estimated intake of vitamin B12 (B= 67.96; β= 0.249; p = 0.002). CONCLUSION: The present findings suggest a high prevalence of vitamin B12 deficiency in metformin-treated diabetic patients. Older patients, patients in long term treatment with metformin and low vitamin B12 intake are probably more prone to this deficiency.